Chapter An integrated approach for marine litter hot spots identification - Farris, Claudia (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Marine litter is defined as any persistent, manufactured or processed solid material discarded, disposed of or abandoned in the marine and coastal environment, and it is among the most important environmental problems which are affecting the sea nowadays. In this work, we present an integrated approach to the marine litter hot spots identification. The results come from a coordinate activity of filed campaigns, satellite monitoring and numerical model simulations. The method has been applied on the Adriatic basin as part of the MARLESS INTERREG IT-HR project.